Art making and the promotion of wellbeing in Samoa – participants' lived experience of a recovery oriented intervention. Issue 2 (4th May 2018) - Fenner, Patricia; Ryan, Brigid; Latai, Leua; Percival, Steven
Abstract: Background: Set in the Pacific nation of Samoa, this study contributes knowledge about art, mental health and trauma recovery for people within a non-Western context. A total of 22 youth and young adults from two residential services participated in a six month weekly art programme set within a health promotion context. Methods: Focus group discussions with staff and consumers explored the participant experience of art making. Focus group data were analysed using Interpretive Phenomenological Analysis (IPA). Results: The study revealed art making in the recovery context supported enhanced levels of self-awareness, a sense of identity, belonging and of being contributors to society. Conclusions: Making art in the group supported participants' sense of voice, empowerment, agency and the capacity to make a social contribution within their respective communities during a period of dislocation from the village and extended family.